(untitled) - Mouterde, Louis Michel Marie; Allais, Florent (Comptes Rendus. Chimie, 2025)
The development and application of biocatalysis have evolved significantly, from the classical use of commercial enzymes to the production, modification and implementation of non-commercially available enzymes, driving advancements in sustainable bioprocesses for bio-based chemical and material production. We have focused on combining chemistry, biocatalysis and process intensification, to create efficient (chemo)enzymatic routes capable of transforming renewable raw materials into valuable industrial products. The portfolio of biocatalysts has been expanded through the integration of biocatalysis and green chemistry principles, facilitating innovative, eco-friendly alternatives to traditional petrochemical processes and supporting the transition towards a circular bioeconomy.